Analisis Korelasi Harga dengan Faktor yang Memengaruhi Mahasiswa dalam Memilih Preferensi Hunian : Studi Kasus Universitas Gadjah Mada - Belatian Detiara; Fidelia Dwipuspita Purwacahya; Alifia Putri Agfani; Nabila Putri Ardevi; Tia Aggrilia; Nurisqi Amalia (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the relationship between price and Universitas Gadjah Mada students in choosing residential accommodations. This study uses correlation methods with the independent variables such as discount, parking area, internet facilities, building quality, and cleanliness and also the dependent variable in the form price. Data refers to primary data from a survey in the form of a questionnaire. The research results show that all variables have an influence on prices and students' decisions in choosing residential preferences. This study also shows that the size of the parking area is the most influential variable on the preferences of Universitas Gadjah Mada students in choosing residential accommodations, where a large parking area increases interest and housing prices. Apart from that, building quality, environmental cleanliness, internet facilities, and discounts also have a significant influence, because they support students' economic, social, and emotional needs, as well as contributing to their comfort and quality of life.